Pengembangan Pop-UP Book Digital Berbasis PowerPoint “PUNAH” Kisah Nabi Nuh A.S. Pembelajaran PAI Kelas 2 SD - Viranti, Nuzha; Azzahra, Fahira; Nurul Muna, Siti Maemunah; Aeni, Ani Nur (Lembaga Yasin AlSys, 2025)
In the digital era, technological advancements pose challenges in education, particularly in providing innovative and interactive learning media. Islamic Religious Education (PAI) in elementary schools still relies heavily on conventional methods such as lectures and textbooks, which often fail to engage students effectively. As a result, students' interest and understanding of the subject matter remain suboptimal. Therefore, innovative and interactive learning media are needed to enhance student engagement in the learning process. This study aims to develop a PowerPoint-based Digital Pop-Up Book, named